2021
DOI: 10.3390/ijerph18147616
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Equivalence between the Original and Estimated Mini-Mental State Examination in People with Dementia

Abstract: Background: The Cognitive Abilities Screening Instrument (CASI) is increasingly used to assess general cognitive function in people with dementia. The Mini-Mental State Examination (MMSE) score can be converted from the CASI (i.e., the estimated MMSE). Recognizing that measurement equivalence is critical to meaningfully representing one with the other, we aimed to determine whether the estimated MMSE score obtained from the CASI was equivalent to the original MMSE in people with dementia. Methods: We obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The CASI was designed based on symptoms diagnosed as dementia and three cognitive screening tools, such as the Mini-Mental State Examination, the Modified Mini-Mental State Test, and the Hasegawa Dementia Screening Scale. The CASI offers two significant advantages: first, it evaluates overall cognitive function with nine dimensions, providing comprehensive cognitive portraits and second, it demonstrates cross-cultural application in measuring global cognitive function and the risk of dementia ( Teng et al, 1994 ; Fitzpatrick et al, 2015 ; Chiu et al, 2021 ). In brief, the CASI includes 25 items representing 9 cognitive domains: attention, concentration, orientation, language, verbal fluency, visual construction, abstraction/judgment, and short- and long-term memory.…”
Section: Methodsmentioning
confidence: 99%
“…The CASI was designed based on symptoms diagnosed as dementia and three cognitive screening tools, such as the Mini-Mental State Examination, the Modified Mini-Mental State Test, and the Hasegawa Dementia Screening Scale. The CASI offers two significant advantages: first, it evaluates overall cognitive function with nine dimensions, providing comprehensive cognitive portraits and second, it demonstrates cross-cultural application in measuring global cognitive function and the risk of dementia ( Teng et al, 1994 ; Fitzpatrick et al, 2015 ; Chiu et al, 2021 ). In brief, the CASI includes 25 items representing 9 cognitive domains: attention, concentration, orientation, language, verbal fluency, visual construction, abstraction/judgment, and short- and long-term memory.…”
Section: Methodsmentioning
confidence: 99%
“…The Mini-Mental State Examination (MMSE) score used in the present study was converted from the CASI, which has been reported to have a moderate to excellent equivalence with the original MMSE score. 12 Diagnosis of AD was based on the NINCDS-ADRDA criteria. 13 Patients with other conditions that may have contributed to the diagnosis of dementia were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…The Charlson comorbidity index (CCI), which contains 19 weighted comorbidities, was also gathered to determine the overall systemic health of each individual ( 21 ). Cognitive performance in the subjects with cognitive decline was assessed by neuropsychologists using 12-item word recall test (total correct trials 1–3, and 15-min delayed free recall) ( 22 , 23 ), estimated Mini-Mental State Examination (MMSE) converted from Cognitive Abilities Screening Instrument ( 24 , 25 ), Montreal Cognitive Assessment (MoCA) ( 26 ), and Clinical Dementia Rating scale ( 27 ). Cognitive performance was documented as well as the contents of diagnostic workups, dementia disorder type, pharmacological and non-pharmacological treatments, and support for the patient from the county.…”
Section: Methodsmentioning
confidence: 99%